High-grade carcinoma with neuroendocrine differentiation of the urinary bladder: A case report of a rare variant - Shashank Bansal; Prutha Jinwala; Aditya Elhence; S P Shrivastava; Vikas Asati; Rajesh Patidar; Prakash G Chitalkar (Annals of Oncology Research and Therapy, 2022)
Neuroendocrine bladder carcinoma is considered a rare variant (<1%) with highly aggressive potential. Because of the rarity of its presentation, available data are mainly from published case reports. A 40-year-old male presented with painless hematuria for the past 3 months. After evaluation, he underwent radical cystectomy with pelvic lymph node dissection with urinary diversion. Histopathology from the postoperative specimen was suggestive of high-grade carcinoma with neuroendocrine differentiation (CK-focal positive, synaptophysin-focal positive, GATA-3, CD-56 positive and Ki-67 85%–90% chromogranin A-negative) stage pT4bN2M0. The case was discussed in the multidisciplinary tumor board and was planned for adjuvant chemotherapy with cisplatin (75 mg/m2) and etoposide (100 mg/m2) Repeated every 21 days. He completed six cycles of adjuvant chemotherapy and was on follow-up. Within 3 months of completing adjuvant therapy, he presented again with a complaint of hematuria and on evaluation found to have a localized recurrence, following which he received radical chemoradiotherapy and is now on follow-up. Our case provides evidence to think us in new dimension, with chemotherapy in adjuvant and radiation in salvage settings instead of adjuvant settings.